English Teacher’s Types of Questions and Students’ Responses in Online Classroom Interaction of Senior High School - Safiani A. Faaroek (Departement of Mathematics Education, 2024)
This research deals with English teacher’s types of questions and students’ responses in online classroom interaction of senior high school. The research was conducted to identify types of questions used by English teacher in teaching English and to know the types of responses used by students in answering teachers’ questions. This research was conducted at SMA Negeri 1 Babalan, Pangkalan Brandan. This research was conducted by using descriptive qualitative method. The data of this research were questions from the teacher to be analyzed based on Thompson and Thornburry theory and students’ responses to be analyzed based on Moskowitz theory. This research was carried out by observing and taking video recording of teaching and learning process. The observations were conducted in eleventh grade students of MIPA 2 in two weeks of lessons. The research findings showed that English teacher at SMA Negeri 1 Babalan used five types of questions, display questions, referential questions, comprehension check, clarification request, confirmation check. The percentage dealing with, display questions 50 times (33.33%), referential questions 31 times (20.66%), comprehension check 34 times (22.66%), clarification request 3 times (2%), and confirmation check 32 times (21.33%). It means that the most dominant type of questions used by the teacher was display question 50 times (33.33%). For students’ types of responses, the research findings showed that the students used five types of responses, students response-specific, open-ended or initiated, confusion, laughter, and silence. The percentage dealing with response-specific 34 times (39.08%), open-ended or initiated 20 times (22.98%), confusion 5 times (5.74%), once laughter (1.15%), and silence 27 times (31.03%). It means the most dominant type of response used students was response-specific 34 times (39.08%).